2015
DOI: 10.1155/2015/846219
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Groups ofEscherichia coliStrains from Patients with Urinary Tract Infection in Iran Based on the New Clermont Phylotyping Method

Abstract: Objectives. In 2013, Clermont classified E. coli strains into eight phylogenetic groups using a new quadruplex PCR method. The aims of this study were to identify the phylogenetic groups of E. coli based on this method and to assess their antibiotic resistance patterns in Bushehr, Iran. Methods. In this cross-sectional study, 140 E. coli isolates were subjected to phylogenetic typing by a quadruplex PCR method. Antimicrobial susceptibility testing was performed by disk diffusion method. Results. Phylogenetic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
54
9
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 26 publications
36
54
9
5
Order By: Relevance
“…Comparing to researchers' results from China, geographically located closest to our country, Luo et al [29] and Cao et al [30] reported the most common phylogenetic group in the UPEC isolates was B2 and D. Our results support these findings. Phylogenetic group A, associated with commensal strains, represented 19.6% of isolates, which was higher than in some studies [31,32], suggesting that the gastrointestinal tract is the main reservoir of strains that may be able to colonize the urinary tract, in accordance with previous observations. UPEC strains encode a number of virulence genes that enable the bacteria to colonize the urinary tract and persist in the face of highly effective host defense [33].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Comparing to researchers' results from China, geographically located closest to our country, Luo et al [29] and Cao et al [30] reported the most common phylogenetic group in the UPEC isolates was B2 and D. Our results support these findings. Phylogenetic group A, associated with commensal strains, represented 19.6% of isolates, which was higher than in some studies [31,32], suggesting that the gastrointestinal tract is the main reservoir of strains that may be able to colonize the urinary tract, in accordance with previous observations. UPEC strains encode a number of virulence genes that enable the bacteria to colonize the urinary tract and persist in the face of highly effective host defense [33].…”
Section: Discussionsupporting
confidence: 89%
“…The rate of MDR in UPEC isolates was 92.5% in India [41]. In another study on UTIs in Iran, the rate of MDR E. coli isolates was 82.1% [31]. MDR causes major consequences such as the empirical therapy of the E. coli infections, as well as a possible co-selection of antimicrobial resistance, which is mediated by the MDR plasmids [41].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that most extra-intestinal pathogenic strains were in group B2, and then group D. It should be noted that the strains belonging to the phylogenetic group B1 was not found among the studied strains in the present study, being similar with the research of Grude et al (2009) The findings are consistent with the results obtained in the study of Bashir et al (2012) in Faisalabad, Pakistan on 59 UPEC isolates from patients, and one study by Abdi et al (2014) on E. coli isolated from UTIs in Sistan region. These were also consistent with the study of Iranpour et al (2015) who studied the phylogenetic typing of strains of E. coli isolated from UTIs, and with the study conducted by Zhao et al (2009) in China on 202 strains of E. coli isolated from UTIs [12][13][14][15].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, a moderate level of multidrug resistance was observed among the strains from group B2, while a low frequency of multidrug resistance was noticed among the isolates belonging to group A. Our findings were in agreement with the results of two separate studies in India and Sweden [20][21], but not with the studies conducted in southern Iran in cities of Shiraz and Bushehr [19,14]. This issue might be due to bacterial characteristics in different geographic regions or use of antibiotics.…”
Section: Discussionsupporting
confidence: 88%
“…No presente trabalho ao aplicar as duas metodologias para a classificação dos grupos A frequência de cada grupo entre os isolados do presente trabalho, utilizando a metodologia preconizada por Clermont et al (2013), foi: A (10%), B1 (9%), B2 (12%), D (27%) e dos novos grupos C (0%), E (4%), F (14%), clado I (16%) e com perfil desconhecido (3%), o quê mostra que esse novo método permite classificar melhor os isolados de E.coli obtidos de águas marinhas do que oriundos de sítios de infecção, uma vez que detectou-se baixa frequência de cepas que não puderam ser classificadas dentro de um grupo específico. Iranpour et al (2015) aplicaram a metodologia de Clermont et al (2013) Além de permitir conhecer melhor a estrutura populacional de E.coli, a determinação dos filogrupos é útil na prática clínica (BINGEN et al, 1998;BOYD;HARTL, 1998;STELL, 2000;PICARD et al, 1999), uma vez que os autores sugerem que há relação entre virulência e grupo filogenético; além de fornecer um método de screening rápido afim de evitar o uso de cepas patogênicas em processos biotecnológicos (CLERMONT; BONACORSI; BINGEN, 2000) e ter aplicação na identificação de principais fontes de contaminação fecal em ambientes aquáticos (AHMED et al, 2011;CARLOS et al, 2010;ORSI et al, 2007).…”
Section: Grupos Filogenéticos E Comparação Entre As Metodologias Propunclassified